(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
Internal audit helps to identify potential risks related to operational activities, financial processes and compliance with legislation. This allows the organization to respond to threats in advance. Auditors conduct risk analysis, assessing their probability and possible consequences. This helps management make informed decisions about which risks require immediate attention.